Peningkatan Toleransi Alumunium pada Jeruk Batang Bawah dengan Teknik Seleksi In Vitro Berulang - Mia Toruan Kosmiatin; Rosa Yunita; Ali Husni (Jurnal AgroBiogen, 2010)
Aluminum Tolerance Improvement of Rootstock Citrusthrough Repeated In Vitro Selection. Mia Kosmiatin,Rosa Yunita, and Ali Husni. National orange productivitywas trend to decrease because of pathogen attack andreducing of planting area. One of alternative ways topreserve and increase orange productivity was usingmarginal soil mainly acid soil. This matter pushed thebreeder to prepare tolerant rootstock and stable in the acidsoil. In vitro culture technique was effective and efficientmethods to produce tolerant and stable rootstock in acid soilthrough simulation of acid soil with addition of highaluminum and low pH in the medium. By the simulation theselection could be done in cell level, so cell was selectedafter induction of variation. A rootstock which highcompatibility with scion, useful rooting, and aluminumtolerance could be increased orange productivity throughacid soil development. The research was conducted in 3phase: (1) induction of embryogenic calli, (2) improvementof genetic variation through mutation, and (3) In vitroselection with AlCl3.6H2O for aluminum and low pH tolerant.Immature embryos of rootstock were use as explant. Theresult showed that the best embryogenic calli were inducedon MS basal medium with MW vitamin + NAA 7,5 mg/l +kinetin 0,5 mg/l. Before selection, 1.000 rad dosage was themost tolerant dosage to growth embryogenic calli. Afterselection, 2.000 rad dosage was the best dosage to produceshoots which stable tolerant to aluminum. Selected 88mutant shoots were produced after three times selection onthe same medium which AlCl3.6H2O added at low pH.